The Role of Vitamin C Supplementation in Periodontal Flap Surgery: A randomized controlled trial - Suman Mukherjee; Sharmistha Dasgupta; Vinayak Gowda (Faculty of Dentistry, Universitas Trisakti, 2023)
Background: A vast literature investigated the role of vitamins in wound healing and pain control. In our study, we explored the role of Vitamin C supplementation for various parameters, post periodontal flap surgery in patients with Chronic Generalized Periodontitis. Objectives: (1) to assess and record the Laundry wound healing index and visual analog scale (VAS) score at 3-, 7-, 14- and 30- days postoperative. (2) To determine the gingival healing and oral hygiene status using plaque index Loe and Silness 1964 (PI), Lobene Gingival index 1986 (GI). (3) To determine and compare the pocket depth (PD) and Clinical attachment level (CAL) with and without supplementation at 3, and 6 weeks postoperative. Methods: A randomized triple-blind study was conducted on 60 patient’s half receiving vitamin C supplementation. The VAS score, wound healing index, PI, GI, PD and CAL were determined and compared at different time intervals. Results: Statistical analysis was done for the recorded data. Chi-square test for Healing index and Friedmann’s test followed by Wilcoxon signed-rank test for VAS showed statistically significant results (P<0.05). Friedmann’s test found a statistically significant (P<0.05) result for the PI score only in the test group. Friedmann’s test found the PI to be statistically significant in the test group (P<0.05). Friedmann’s test followed by Wilcoxon signed-rank test found the PD and CAL to be statistically significant (P<0.05) at all different time intervals. Conclusion: In the study, vitamin C supplementation enhanced wound healing and lessened postoperative pain. An instant benefit of vitamin C supplementation was found in this study. A prolonged supplementation and further studies with a considerable sample size would justify the use of vitamin supplementation.